Genetic improvement of indigenous Greek sheep and goat breeds - ARGYRIADOU, A.; GELASAKIS, A. I.; BANOS, G.; ARSENOS, G. (Journal of the Hellenic Veterinary Medical Society, 2020)
The objective of the study was twofold: (i) to review the genetics of production and resilience traits of indigenous Greek small ruminant breeds as well as the evolution of national breeding programs, and (ii) explore innovative and feasible approaches to overcome the challenges and constraints towards improving these breeds and enhancing the sustainability of the small ruminant sector. Previous studies on the genetic basis of production and resilience traits of indigenous breeds revealed high improvement potential. However, the lack of follow-up action has failed to produce applicable results. Thus, implementation of scientific findings in existing breeding programs for these breeds is extremely limited. The latter has contributed to the overall poor success of such programs. Furthermore, due to the fact that most farmers do not comprehend the strategic importance of genetic improvement and lack motivation for self-funding, breeding programs have mostly relied on European or government funding; the latter has resulted in intermittent implementation. Therefore, most programs failed to improve performance of indigenous Greek breeds, many of which were consequently replaced by foreign breeds of higher productivity and documented merit. In order to facilitate the design of breeding schemes and overcome the challenges towards improvement of indigenous breeds, an integrative approach is necessary. The latter should be based on identification of specific breeding objectives, reflecting the priorities and needs of the sector, as well as the capacity of the indigenous populations. Scientific advances exemplified by genomic selection and novel reproductive technologies will enable faster and more effective genetic improvement. The overall approach is expected to enhance the competitiveness of indigenous Greek small ruminant breeds and the sustainability of the sector.